2020
DOI: 10.2337/dc20-1318
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Dependent Insulinotropic Peptide in the High-Normal Range Is Associated With Increased Carotid Intima-Media Thickness

Abstract: OBJECTIVE While existing evidence supports beneficial cardiovascular effects of glucagon-like peptide 1 (GLP-1), emerging studies suggest that glucose-dependent insulinotropic peptide (GIP) and/or signaling via the GIP receptor may have untoward cardiovascular effects. Indeed, recent studies show that fasting physiological GIP levels are associated with total mortality and cardiovascular mortality, and it was suggested that GIP plays a role in pathogenesis of coronary artery disease. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Total plasma GLP-1 concentrations (intact GLP-1 and the metabolite GLP-1 9–36 amide) were determined radio immunologically as described previously 19 (minimum detection limit 1 pmol/L; intra- and inter-assay coefficients of variation < 6.0% and < 15%, respectively). Identical quality controls and identical batches for all reagents in each analysis set were used in a consecutive sample analysis for two months.…”
Section: Methodsmentioning
confidence: 99%
“…Total plasma GLP-1 concentrations (intact GLP-1 and the metabolite GLP-1 9–36 amide) were determined radio immunologically as described previously 19 (minimum detection limit 1 pmol/L; intra- and inter-assay coefficients of variation < 6.0% and < 15%, respectively). Identical quality controls and identical batches for all reagents in each analysis set were used in a consecutive sample analysis for two months.…”
Section: Methodsmentioning
confidence: 99%
“…Further, cardiac selective knockout of the GIPR was not protective in experimental models of heart failure ( 25 ). In contrast with these preclinical experimental findings, recent evidence suggests that fasting GIP levels are associated with increased carotid intimal thickening ( 26 ). In addition, evidence from a recent meta-analysis ( 27 ) of two large population-based cohort studies suggests that higher fasting but not postchallenge GIP levels were associated with increased risk of CVD mortality (hazard ratio 1.30; 95% CI 1.11, 1.52; P = 0.001).…”
Section: Introductionmentioning
confidence: 95%
“…Following this observation, two prospective studies of independent populations, Malmö Diet Cancer–Cardiovascular Cohort (MDC-CC) and Prevalence, Prediction, and Prevention of Diabetes in Botnia (PPP-Botnia), have demonstrated that high fasting levels of GIP, but not GLP-1, are associated with an increased risk for coronary artery disease, myocardial infarction, and cardiovascular and all-cause death [ 83 ]. In participants of MDC-CC at re-examination, GIP and GLP-1 fasting levels proved to be divergent in association with markers of subclinical atherosclerosis: increased fasting GIP levels were associated with increased intima-media thickness in the common carotid artery and in the carotid bifurcation, while GLP-1 was associated with decreased intima-media thickness in the carotid bifurcation [ 84 ].…”
Section: Gut Molecules and Cardiovascular Diseasesmentioning
confidence: 99%